Development of an Interactive Learning Tool Based on the CANVA App for Teaching the Pythagorean Theorem to Eighth-Grade Students at Junior High School 12 Satap Tibawa - Findi Alfionita Yusuf; Sarson W. Pomalato; Nursiya Bito (International journal of technology and education research, 2026)
Canva is one of the apps that offers an easy alternative for designing. One of Canva’s key advantages is that it makes it easy to create any kind of design—presentations (PowerPoint), graphics, ebook covers, videos, and infographics—using built-in animations, all of which can be published immediately anywhere. Given the issues at Junior High School 12 Satap Tibawa, the researcher was motivated to conduct research and development (R&D) using interactive learning materials based on Canva. One way to leverage advanced technology in education is through educational media that can help students understand the Pythagorean theorem, such as Canva-based interactive educational media. The purpose of this study is to examine the development and outcomes of an interactive learning medium based on the Canva application for teaching the Pythagorean theorem to eighth-grade students at Junior High School 12 Satap Tibawa. The type of research used is Research and Development (R&D). Sugiiono (2016:297) states that the R&D research method is used to develop specific products and test their effectiveness. The purpose of this study is to develop interactive learning materials on the Pythagorean Theorem for eighth-grade junior high school students. Results of the Research and Development of an Interactive Learning Medium Based on the Canva Application for the Pythagorean Theorem in Grade 8 at Junior High School 12 Satap Tibawa. Consequently, it can be concluded that the results of the development of an interactive learning medium based on the Canva application for the Pythagorean Theorem unit in Grade 8 at Junior High School 12 Satap Tibawa fall into the “very good” category and can be used in the classroom.